Culturally Responsive Pedagogical Knowledge: An Integrative Teacher Knowledge Base for Diversified STEM Classrooms - Justina A. Ogodo (MDPI AG, 2024)
Teaching can be challenging, especially when teachers are under-prepared to enter a workforce with a constantly changing landscape. Preparing teachers for STEM content has generated multiple approaches from varying perspectives. While some scholars advocate for content expertise, others promote pedagogy or social context as approaches for translating STEM content for students. Yet, many contend that teachers must be culturally knowledgeable to respond to student diversity effectively. While these arguments are valuable and needed, many have not considered the interconnectedness of these approaches, often used in silos. This conceptual paper unpacks some of these arguments using the social constructivism theory of learning as the epistemic lens to examine and interpret what STEM teacher knowledge should encompass in the 21st-century diversified classroom. After thoroughly evaluating the core elements of three commonly used teacher constructs, this paper presents an integrative, holistic teacher knowledge-culturally responsive pedagogical knowledge (CRPK) framework that considers the necessary qualities that teachers must possess that are functional, content-focused, and pedagogically inclusive. The proposed CRPK construct would be a valuable programmatic tool for teacher preparation, curriculum development, and classroom praxis.